Inhibition of Nitrosative Stress Attenuates Myocardial Injury and Improves Outcomes after Cardiac Arrest and Resuscitation. Issue 6 (25th June 2022) - Wang, Fulin; Yuan, Qiuhuan; Cao, Shengchuan; Li, Ruochuan; Zhang, Jian; Yang, Kehui; Xu, Feng; Chen, Yuguo
ABSTRACT: Objectives: Nitrosative stress is widely involved in cell injury via inducing the nitration modification of a variety of proteins. This study aimed to investigate whether inhibition of nitrosative stress attenuated myocardial injury and improved outcomes in a rat model of cardiac arrest (CA) and cardiopulmonary resuscitation (CPR). Methods: Adult male Wistar rats were subjected to asphyxia-induced cardiac arrest and subsequently resuscitation. One minute after return of spontaneous circulation (ROSC), rats were randomized and administered the nitrosative stress inhibitor, FeTMPyP (1 or 3 mg/kg), or normal saline as a placebo. 3-Nitrotyrosine (3-NT), mean arterial pressure (MAP), heart rate (HR), mortality, electrocardiogram (ECG), left ventricular ejection fraction (EF) and fractional shortening (FS), and levels of myocardial apoptosis were evaluated. The concentrations of lactate, creatine kinase MB isoenzyme (CK-MB), and angiotensin II (Ang II), were measured in blood samples. Results: 3-NT level was significantly increased in the heart after ROSC. Administration of FeTMPyP (1 or 3 mg/kg) attenuated the increase of 3-NT in the myocardium. Inhibition of nitrosative stress improved survival and attenuated CA/CPR-induced reperfusion injury by maintaining the stability of MAP and HR, and reducing the accumulation of lactic acid. Post-cardiac arrest rats had higher serum CK-MB and Ang II than healthy rats, while EF and FS were lower in healthy rats. Inhibition of nitrosative stress not only alleviated ischemic heart injury but also reduced the occurrence of CA/CPR-induced of arrhythmias. Moreover, nitrosative stress mediated the upregulation of Cleaved caspase-3 and downregulation Bcl-2, which was abolished by FeTMPyP. Conclusions: Inhibition of nitrosative stress is a novel molecular target to alleviate myocardial injury and improve outcomes in a rat model of CA/CPR.